“Do the People Benefit from Being Deceived?” A Debate on the Politics of the Enlightenment - Décultot, Elisabeth (The Historical Review/La Revue Historique, 2023)
In 1777, the Royal Prussian Academy of Sciences published its prize question for the year 1780: “Est-il utile au Peuple d’être trompé, soit qu’on l’induise dans de nouvelles erreurs, ou qu’on l’entretienne dans celles où il est?” Whether the people drew benefit from being deceived, either by being induced into new errors, or by being maintained in existing ones: the question attracted 42 essays, the largest number ever received for a Prussian Academy contest in the eighteenth century. This paper analyses the genesis and the course of this contest. To this end, it will begin by tracing the evolution of Frederick the Great’s political thought regarding the interrelation of people, the art of governing and deceit; it will then examine the status of this contest in the history of the Academy, before lastly focusing on one of the two winning entries and its relationship to the idea of enlightenment.